THE IMPLEMENTATION OF UNIVERSAL BASIC EDUCATION: THE JOURNEY SO FAR IN BORNO, BAUCHI AND TARABA STATES, NIGERIA - Bukar, I. B.; Mwajim, A. U.; Kadiri, Dugje (Sokoto Educational Review, 2017)
This paper examined the implementation of Universal Basic Education programme in Borno, Bauchi and Taraba states, Nigeria. The major problems that the paper looked at include lack of infrastructural facilities, storage of teaching and learning material and qualified teachers. Observation and documented evidence from the three Ministries of Education, Local Education Authorities and Universal Basic Commission were used in collecting the data. The study revealed that some of the teachers recruited to participate in the programme had fake certificates. This was discovered through verification of results by the UBE commission in Borno state. Despite the problems observed, the UBE has in the three states employed over 7.000 teachers as well as built and renovated classrooms. It was recommended, among other things that, statistical information on the components that makes teaching and learning effective should be considered before embarking on such an important educational programme for the nation.